Abuso sexual na infância e uso de cocaína na vida adulta: uma relação íntima - Bragiato, Emi Carneiro [UNIFESP] (2018)
Objective: To investigate the association between the occurrence of sexual abuse in childhood and the development of dependence on snorted or smoked cocaine (crack) in adult life. Methods: This is an observational and retrospective study whose sample is based on a data collected from medical records obtained between 2008 to 2016. A descriptive statistical analysis and a study of the association between explanatory and demographic data, sexual abuse in childhood with the outcome (use of smoked or aspirated cocaine) wereas carried out. Then, a logistic regression was used to analyze the associations. Results: Among men, 13.5% reported having been sexually abused, and among women 36%. Those who used crack or snorted cocaine were 65.3% of the sample (n = 405). Men were more likely to be cocaine users than women (OR = 2.68; CI95%: 1.435.01; p = 0.002); participants who suffered sexual abuse in childhood were more likely to be in the group of cocaine users. (OR = 2.47, 95% CI: 1.324.61, p = 0.003). Conclusion: The prevalence of drug users with a history of childhood sexual abuse is high and it is necessary for centers specialized in the treatment of these patients to investigate the occurrence of sexual violence in childhood or adolescence. Although child sexual abuse is a major problem with harmful consequences, very little progress has been made in discussing and developing public policies that can protect the abused child or adolescent.